Human Rights Review on Age Limitation of Candidates for Regional Heads - Syafrizal Syafrizal; Fikri Aulia Akmal; Sunardi Purwanda (Amsir Law Journal, 2024)
Constitutional Court Decision Number 70/PUU-XXII/2024 is the result of a judicial review of Law Number 10/2016 on the Second Amendment to Law Number 1/2015 regulating the minimum age limit for regional head candidates. The regulation is discriminatory because it limits the political participation of younger individuals. This article seeks to critically answer how human rights studies view the age limit in Constitutional Court Decision Number 70/PUU-XXII/2024. The method used in this research is a normative legal research method with an analytical-critical approach and case studies that prioritize human rights aspects. The Constitutional Court explained that although age restrictions can be justified, this policy must be evaluated periodically to ensure its relevance and suitability with the evolving social and political dynamics. The Constitutional Court also emphasized the importance of flexibility in this arrangement, in order to avoid age discrimination that could harm certain groups, especially the potential younger generation. Public policies must be responsive to demographic and social changes, including in terms of political participation. This policy should be aligned with the principles of equality and human rights, and should take into account the ability and integrity of candidates without being hampered by rigid age limits. Therefore, recommend a policy that is more flexible and responsive to social dynamics. ___ References Books with an author: Al-Mahalli, J., & As-Suyuthi, J. (2018). Terjemahan Tafsir Jalalain Jilid I, Jakarta: Senja Media Utama. Jalaluddin al-Mahaly, A., & Jalaluddin as-Suyuthi. (1998). Tafsir al-Qur’an al-Karim. Beirut: Daar al Fikr. Journal articles: Anggreni, D., Fuadi, A., Fitriyani, F., & Al-Kautsar, M. I. (2024). Peran Mahkamah Konstitusi dalam Menjamin Kedaulatan Hukum di Indonesia. Hutanasyah: Jurnal Hukum Tata Negara, 3(1), 11-26. https://doi.org/10.37092/hutanasyah.v3i1.868 Dasyah, F., & Desiandri, Y. S. (2023). Integrasi Nilai Hak Asasi Manusia dalam Proses Pemilihan Umum di Indonesia. Jurnal Pendidikan Tambusai, 7(3), 29156-29161. https://doi.org/10.31004/jptam.v7i3.11663 Gemalmaz, H. B. (2018). Democracy, Free Elections and Independent Candidates: Critical Remarks on The Jurisprudence of The European Court of Human Rights. Journal of Istanbul University Law Faculty, 76(1), 9-63. https://dergipark.org.tr/en/pub/iuhfm/issue/39991/465155 Giyandri, T. F., & Sinaga, J. B. B. (2024). Tantangan dan Dinamika Penerapan Teori Politik Kontemporer di Indonesia. Jurnal Ilmu Hukum, Humaniora dan Politik, 4(3), 371-378. https://doi.org/10.38035/jihhp.v4i3.1919 Gusman, D. G., Nazmi, D. N., & Syofyan, Y. S. (2022). Pemenuhan Hak Memperoleh Pekerjaan bagi Penyandang Disabilitas berdasarkan Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas. Riau Law Journal, 6(2), 231-245. http://dx.doi.org/10.30652/rlj.v6i2.7963 Hidayat, A., Haykel, M., Alhaddi, R. U., Selviana, S., & Delvina, S. (2024). Analisis Yuridis terhadap Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Dikaitkan dengan Mahkamah Konstitusi sebagai Positif Legislator. Hukum Inovatif: Jurnal Ilmu Hukum Sosial dan Humaniora, 1(3), 79-95. https://doi.org/10.62383/humif.v1i3.292 Joseph, S. (2019). Extending the right to life under the International Covenant on Civil and Political Rights: General Comment 36. Human Rights Law Review, 19(2), 347-368. https://doi.org/10.1093/hrlr/ngz003 Peramesti, N. P. D. Y., & Kusmana, D. (2018). Kepemimpinan Ideal pada Era Generasi Milenial. Transformasi: Jurnal Manajemen Pemerintahan, 10(1), 73-84. ttps://doi.org/10.33701/jt.v10i1.413 Prasetio, D. E. (2022). Rekonstruksi Subjectum Litis Pembubaran Partai Politik sebagai Perlindungan Hak Politik Warga Negara. Sol Justicia, 5(1), 18-37. https://doi.org/10.54816/sj.v5i1.474 Purwanda, S. (2020). The Existence of the Right to Books for Frontier, Outermost and Disadvantaged Regions as Part of the Right to Enjoy Education. JL Pol'y & Globalization, 95, 42. https://doi.org/10.7176/JLPG/95-07 Purwanda, S., Ambarwati, A., Darmawati, D., & Prayudi, P. (2024). Haluan Kesejahteraan Sosial dalam Diskursus Teori-Teori Keadilan. Dinamika Hukum, 25(1), 152-161. https://doi.org/10.35315/dh.v25i1.9819 Purwanda, S., & Wulandari, A. S. R. (2023). Socio-Legal Studies: Methodical Implications of Legal Development in Indonesia. Al-'Adl, 16(2), 152-163. http://dx.doi.org/10.31332/aladl.v16i2.6129 Razak, A. (2023). Reformulasi Pemimpin Usia Muda sebagai Calon Presiden dan Wakil Presiden: Tinjauan Ius Constituendum. Risalah Hukum, 19(2), 61-75. https://e-journal.fh.unmul.ac.id/index.php/risalah/article/view/1339 Rohmah, E. I. (2024). Dinamika Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 tentang Persyaratan Usia Calon Presiden dan Wakil Presiden. Progresif: Jurnal Hukum, 18(1), 100-131. https://doi.org/10.33019/progresif.v18i1.4636 Salim, H., & Rowa, I. R. (2024). Pembatasan Hak Asasi Manusia dalam Putusan Mahkamah Konstitusi. Jurnal Ilmiah Multidisiplin Unika, 1(1), 16-27. https://journal.fsei.unikamamuju.ac.id/index.php/AL-ILMU/article/view/3 Sanger, B. G. (2019). Perlindungan Hak Politik Perempuan sebagai Hak Asasi Manusia dan Pengaturannya dalam Konvensi Internasional. Lex Et Societatis, 7(3), 163-171. https://doi.org/10.35796/les.v7i3.24689 Sanmas, R. (2024). Kajian Hukum Konstitusi terhadap Putusan Mahkamah Konsitusi Terkini: Usia Calon Presiden dan Calon Kepala Daerah. Birokrasi: Jurnal Ilmu Hukum dan Tata Negara, 2(4), 23-34. https://doi.org/10.55606/birokrasi.v2i4.1508 Utomo, N. A. (2016). Mengurai Kerangka Legislasi sebagai Instrumen Perwujudan Hak Asasi Manusia. Jurnal Konstitusi, 13(4), 886-910. https://doi.org/10.31078/jk13410 World Wide Web: Suyanto, B. (ed.). (2024). Mahasiswa Gugat Penetapan Syarat Usia Calon Kepala Daerah ke MK. Available online from: https://www.antaranews.com/berita/4195503/mahasiswa-gugat-penetapan-syarat-usia-calon-kepala-daerah-ke-mk .